Surgical Treatment Of Achilles Tendon Injuries By The Transposition Method Of Flexor Tendon Of Long Finger 1 (Eurasian Medical Research Periodical, 2024)
In this article, one of the important injuries for Traumatologists and Orthopedists is the selection of the treatment method for chronic injuries of the Achilles tendon, improvement of the operative treatment technique and the treatment of chronic injuries - prevention of limitation of activity in the love joints and study of early rehabilitation methods and methods of treatment of these pathologies with our experiences and longterm postoperative results are presented